Prarancangan Pabrik Akrolein Dari Gliserol Dengan Desain Alat Utama Reaktor Fixed Bed Multitube Pada Proses Dehidrasi Gliserol - Sari, Ronna Puspita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Acrolein (C3H4O) is the simplest unsaturated aldehyde compound but is highly toxic and high reactivity due to the conjugation of a carbonyl group with a vinyl group. The uses of acrolein is protecting liquid fuels from microorganisms, making essential amino acid methionine and as a good separator and dispersing agent which is widely used in the ceramic, paper and electroplating industries. The acrolein plant is design to produce 36.000 tons/years. One of the main equipment in this plant is the dehydration reactor to react glycerol to produce acrolein. The type of reactor is fixed bed multitube reactor using WO3/ZrO2 as a catalyst at 410℃ and 1 bar in isothermal conditions. The glycerol flow rate is 21.088,193 kg/h and the cooling water flow rate is 113.891,47 kg/h. The height of reactor is 8,23 m and the diameter is 2,39 m with torispherical flanged and dished head and lug support.Keywords: acrolein, fixed bed multitube reactor, glycerol, zirconium.